Migrants’ housing: bridging human rights and sustainable development goals for inclusive communities - Nor Suzylah Sohaimi; Rosfaraliza Azura Ramli (Penerbit Universiti Kebangsaan Malaysia, 2023)
The United Nations issued the Universal Declaration of Human Rights in 1948 and the International Covenant on Economic, Social, and Cultural Rights in 1966. Both recognise the right to an acceptable living standard, which includes appropriate housing. Characteristics of sufficient housing include affordability, habitability, accessibility, location, cultural appropriateness, and access to resources such as services, materials, utilities, and infrastructure. However, housing and migrant settlement challenges have persisted in Malaysia due to a shortage of living space, poor government policies, and societal humiliation. This forces many migrants to live in crowded and unsafe conditions. Surprisingly, compared to other integration initiatives, little attention has been given to the housing component of the integration of regular migrants. This complacency and fragility affect both natives and migrants. The 17 Sustainable Development Goals (SDGs), especially SDG 11: Sustainable Cities and Communities, provide important guiding concepts that support the right to an acceptable standard of life, which includes adequate housing.